KONTRIBUSI KEPEMIMPINAN MANAJER TERHADAP DISIPLIN KERJA KARAYAWAN DI SALON BEAUTY LOUNGE PADANG - Asisifa, Ummi Nur (journal of residu, 2019)
One salon that emphasizes discipline is Beauty Lounge, based on the writer's observation during the Industrial Field Experience in January to March 2019 in the Beauty Lounge work environment, there are still employees who break the rules. This study aims to a) determine the level of achievement of managers' leadership respondents, b) the level of attainment of respondents in employee work discipline, c) the manager's leadership contribution to the work discipline of Beauty Lounge Padang employees.This type of research is quantitative descriptive with causal associative methods. The research was carried out in September to completion at the Padang Beauty Lounge salon. The population is all employees in the Padang beauty lounge, amounting to 32 people. The data collection technique is using a questionnaire adjusted in the form of a Likert scale that has been tested for validity and reliability. The data analysis technique uses the Simple Linear Regression test.Based on the results of the study note the level of achievement of respondents on the HRD Manager leadership variables there are 62.50% of respondents included in the good category, 31.25% very good category and 6.25% of respondents with enough categories, work discipline variables there are 53.13% of respondents included in the category good, 40.63% category is very good and 6.25% of respondents with enough category and contribution between HRD Manager leadership on employee work discipline, the regression coefficient equation is obtained by 0.392 with a sig value of 0.03 <0.05, the value of R square of 0.266 (26.6%).It is expected that the hotel leadership in making decisions is always right and fast so that all decisions taken can benefit businesses and employees and conduct periodic evaluations for the progress of the salon.